RP-HPLC Method for Estimation of Flucloxacillin Magnesium and Sodium Benzoate in Oral Suspension - GOWRI SANKAR, D.; RAJESWARI, A.; NAGESH BABU, A.; VAMSI KRISHNA, M. (Asian Journal of Chemistry, 2010)
A simple, sensitive and precise reversed phase high performance liquid chromatographic (RP-HPLC) method has been developed for the estimation of flucloxacillin magnesium and sodium benzoate (preservative) in oral suspension. The quantification was carried out using a Kromasil 100, C-18 column, 150 mm × 4.6 mm i.d. and 5 μm particle size in gradient mode with mobile phase comprising pH 5.0 phosphate buffer and acetonitrile at a flow rate of 1.5 mL/min. The eluent was monitered at 225 nm. The retention time of the drug was 10.9 min and of the sodium benzoate (preservative) was 2.02 min. The calibration curve was linear in the concentration range of 10-150 μg/mL. The proposed method was statistically evaluated and can be applied for routine quality control analysis of flucloxacillin magnesium and sodium benzoate in oral suspension.